Effect of Filling of Red Mud on the Dielectric Constant of Polymethyl Metharcrylate - Mittal, Alok; Jain, Vinneta; Mittal, Jyoti (Asian Journal of Chemistry, 2010)
The paper describes the effect of red mud filler on dielectric constant of polymethyl methacrylate. The studies were carried out in the temperature range 35-80°C and frequency range 400 Hz to 100KHz. The results also show that the filling of red mud increases the magnitude of dielectric constant of polymethyl methacrylate.